Panel data regression approach on inclusive green growth - E. Juniardi; S. Amar; H. Aimon (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study is investigated on endogenous variables inclusive of green growth by developing the concept of inclusive green growth in Indonesia. The objective of the current study was to describe the conditions of inclusive green development in each province in Indonesia, which is due to the unavailability of data describing the conditions of inclusive green development.METHODS:  This study used time series data from 2011-2019, and cross section data of 34 provinces, which were analyzed using panel data regression research methods. The novelty of this study is the use of environmental quality variables to replace environmental degradation in calculating the composite variable of inclusive green growth.  The determinants of inclusive green growth used in this study were inclusive human development, regional independence, infrastructure, crime, industrialization and natural disasters.FINDINGS: The important study findings were inclusive human development, regional financial performance, infrastructure and natural disasters have a significant positive effect on inclusive green growth in Indonesia. On the other hand, industrialization had a significant negative effect on inclusive green growth in Indonesia, while crime did not have a significant effect on inclusive green growth in Indonesia. Simultaneously, inclusive human development, regional independence, infrastructure, crime, industrialization and natural disasters had a significant impact on inclusive green growth in Indonesia.CONCLUSION: The second hypothesis in this study proved to be accepted. Meanwhile, the first hypothesis is not entirely accepted. Therefore, it is highly recommended for the provincial government in Indonesia to intervene on the variables of inclusive human development, regional financial performance, infrastructure, industrialization and natural disasters to increase inclusive green growth. Meanwhile, for future researchers, it is recommended to find other variables that contribute in achieving inclusive green growth.